2009
DOI: 10.1186/1756-9966-28-10
|View full text |Cite
|
Sign up to set email alerts
|

MUTYH Gln324His gene polymorphism and genetic susceptibility for lung cancer in a Japanese population

Abstract: Background: Genetic polymorphisms of DNA repair enzymes in the base excision repair (BER) pathway, may lead to genetic instability and lung cancer carcinogenesis. We investigated the interactions among the gene polymorphisms in DNA repair genes and lung cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 19 publications
1
38
0
Order By: Relevance
“…To the best of our knowledge, there are no reports indicating a correlation of the 972G>C SNP of the MUTYH gene with the occurrence of neurodegenerative changes. However, there are a number of reports about the relationship between this polymorphism and the carcinogenesis process [32,33]. …”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, there are no reports indicating a correlation of the 972G>C SNP of the MUTYH gene with the occurrence of neurodegenerative changes. However, there are a number of reports about the relationship between this polymorphism and the carcinogenesis process [32,33]. …”
Section: Discussionmentioning
confidence: 99%
“…A SNP Gln324His which was extensively studied in Japanese populations was found to be functionally relevant and to be associated with colon cancer [44,45]. However, for lung cancer, only one study reported increased risk for individuals carrying the variant His/His genotype compared with those with the Gln/Gln genotype; another one showed no association [13]. Thus, it was not surprising that BER polymorphisms did not show strong associations with lung cancer as those we observed in NER although some interactions between BER and NER polymorphisms were observed in our study.…”
Section: Discussionmentioning
confidence: 99%
“…BER, NER and DSB are three well-known DNA repair pathways which are mainly responsible for the repair of minor base alterations, removal of UV damage, bulky DNA adducts and recombination of homologous or non-homologous end-joining [1,2]. Many studies have investigated the associations of lung cancer with the genetic polymorphisms involved in these pathways in different populations [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. However, the study findings were inconsistent due to either small sample size or populations with mixed genetic backgrounds.…”
Section: Introductionmentioning
confidence: 99%
“…Recent researches have demonstrated that many genes play pivotal roles in the pathogenesis of AE. Numerous studies have shown that damage repair genes play critical role in the pathogenesis (Miyaishi et al, 2009;Sliwinski et al, 2009;Picelli et al, 2010;Stanczyk et al, 2011;Santos et al, 2012), indicating the important relationship between the gene MUTYH and AE. The main finding of this study is that the same association dose exist in Han Chinese population.…”
Section: Discussionmentioning
confidence: 99%